Post-Brexit Europe and UK
XIV, 192 p. 5 illus.
Keywords: This book discusses how tensions and unknowns may impact future relations between a post-Brexit UK, the EU and the countries of the Gulf, including Iran. The authors of this book consider, in different ways, whether British and EU27 relations with the Gulf States may change or whether the traditions and the weight of their history reinforce the preexisting patterns of these relationships. Ongoing changes in the Gulf, the present disputes and the trajectories economic reform also influence these discussions. The book analyses the changing positions of the US, China and Russia that are likely to impact Europe’s interests. It explores outcomes of ongoing world challenges, such as the COVID-19 pandemic and the crash of oil prices, to further examine Post-Brexit Europe and UK policy challenges towards Iran and the GCC States. Dr. Geoffrey Edwards, Emeritus Reader in European Studies, University of Cambridge, Department of Politics and InternationalStudies, and Emeritus Fellow Pembroke College Cambridge and Jean Monnet Chair in Political Science Dr. Abdullah Baabood is a graduate in business studies and international relations. He holds a Master in Business Administration (MBA), a Master in International Relations (MA) and a Doctorate in International political Economy (PhD) at Cambridge University. He particularly focuses on the states of the Gulf Cooperation Council (GCC) and their economic, social and political development as well as external relations. Dr. Diana Galeeva is currently an Academic Visitor to St Antony’s College (Oxford University), having previously also been a Scholar-in-Residence at the Oxford Centre for Islamic Studies. She completed her PhD at Durham University (UK). Her research interests include International Relations theory, Gulf Cooperation Council states’ foreign policies, and Russia and the Middle East.